Investigation of depth selective Raman spectroscopy. - Tan, Shi Ying (2012)
One of the most common skin cancers such as basal cell carcinoma (BCC) is caused by over exposure of ultra-violet (UV) rays from the sun. Conventional way of diagnosis of any suspicious lesion under the skin is commonly carried out by biopsy which is an invasive method that requires an expertise to remove a piece of tissue from the patient and followed with histopathology examination. This study aims to demonstrate the feasibility of Raman spectroscopy on the depth-resolved measurement to analyze suspicious lesions under the skin using tissue phantoms. Multi-layered tissue phantom model consisted of two layers with different thickness were fabricated to comprehend the depth-resolved measurement. Raman scatterers such as rhodamine 6G (R6G) of 10-3M and urea of 3M were used to produce distinct peaks for identification. The two layers also included nigrosin as the light absorber and intralipid as the light scatterer to mimic real human skin optical properties. Experiments conducted to retrieve the Stokes Raman spectra and results were analyzed. Results from Stokes Raman spectra of the two layered tissue phantom shown that Raman spectroscopy has the potential for depth resolved measurement as well as for skin cancer diagnosis. In this study, an equation was proposed to correlate the raw and intrinsic spectra to predict the depth of suspicious lesion under the skin.